A novel electrochemical sensor for glyphosate detection based on Ti3C2Tx/Cu-BTC nanocomposite. Issue 9 (10th February 2022) - Wang, Shan; Yao, Yanqing; Zhao, Jia; Han, Xuhui; Chai, Chunpeng; Dai, Pei
Abstract : The Ti3 C2 T x /Cu-BTC nanocomposite exhibits excellent sensing performance for glyphosate with a low detection limit and wide detection range. Moreover, the electrochemical sensor also shows excellent selectivity, good reproducibility and stability. Abstract : The copper benzene-1, 3, 5-tricarboxylate (Cu-BTC) with outstanding chemical and physical properties, is a novel and promising material in the field of electrochemical sensing. However, it has significant limitations for direct application in electrochemical sensing due to the relatively weak conductivity of Cu-BTC. Here, the conductivity of Cu-BTC was improved by loading Cu-BTC onto two-dimensional Ti3 C2 T x nanosheets with high conductivity. Thanks to the synergistic effect produced by the high conductivity of Ti3 C2 T x and the unique catalytic activity of Cu-BTC, the Ti3 C2 T x /Cu-BTC nanocomposite exhibits excellent sensing performance for glyphosate, with a low limit of detection (LOD) of 2.6 × 10 −14 M and wider linear sensing range of 1.0 × 10 −13 to 1.0 × 10 −6 M. Moreover, the electrochemical sensor based on Ti3 C2 T x /Cu-BTC also shows excellent selectivity, good reproducibility and stability.